Diverse reactions of aquaculture biofilter biofilms following acute high-dose peracetic acid - Qi, Wanhe; Aalto, Sanni L.; Skov, Peter Vilhelm; de Jesus Gregersen, Kim João; Pedersen, Lars-Flemming (Elsevier, 2025)
Peracetic acid (PAA) is an effective disinfectant in aquaculture systems to reduce pathogen loads and improve water quality. However, its effectiveness in disinfecting biofilm in recirculating aquaculture systems (RAS) and resetting biofilters between productions remains unknown. This study evaluated the effects of acute PAA exposure on biofilter biofilms from freshwater RAS. Identical types of bioelements were collected from a pilot-scale RAS (without prior PAA treatment) and a commercial RAS (with PAA treatment), and exposed to PAA concentrations of 0, 1, 2, 4, 8, and 16 mg/L for 1 h. Microbial activity and viability of the exposed biofilms were evaluated using respirometry and flow cytometry. Results showed dose-dependent inhibition of biofilm activity and viability in the pilot-scale RAS. Nitrite oxidation was the most sensitive process to PAA, with an IC50 of 1.27 mg/L (the concentration at which PAA inhibited biofilm metabolic activity by 50 %), followed by ammonia oxidation (IC50 = 1.59 mg/L) and endogenous respiration (IC50 = 2.67 mg/L). Microbial activity linked to H2O2 decomposition was least affected (IC50 = 4.68 mg/L). Live cell counts decreased from 9.1 × 107 counts/cm2 to 2.4 × 107 counts/cm2 of bioelement surface, with dead cells proportion increasing from 15 % to 54 %. In contrast, biofilter biofilms from the commercial RAS exhibited significantly lower sensitivity to PAA dosage, with reductions in nitrite oxidation (39 %) and ammonia oxidation (51 %) observed only at 16 mg/L compared to control. These findings suggest that routine PAA exposure, as part of the other operating conditions on the commercial RAS, can enhance the biofilm's sensitivity to PAA. The study provides new insight into the sensitivity of aquaculture biofilm to PAA treatment and its effect on associated microbial processes.
Keywords: disinfection; RAS; microbial inhibition; nitrification; flow cytometry; respirometry